Reliable and valid assessment of competence in endoscopic ultrasonography and fine-needle aspiration for mediastinal staging of non-small cell lung cancer - Konge, L.; Vilmann, P.; Clementsen, P.; Annema, J. T.; Ringsted, C. (Endoscopy, 2012)
Background and study aims: Fine-needle aspiration (FNA) guided by endoscopic ultrasonography (EUS) is important in mediastinal staging of non-small cell lung cancer (NSCLC). Training standards and implementation strategies of this technique are currently under discussion. The aim of this study was to explore the reliability and validity of a newly developed EUS Assessment Tool (EUSAT) designed to measure competence in EUS – FNA for mediastinal staging of NSCLC.Patients and methods: A total of 30 patients with proven or suspected NSCLC underwent EUS – FNA for mediastinal staging by three trainees and three experienced physicians. Their performances were assessed prospectively by three experts in EUS under direct observation and again 2 months later in a blinded fashion using digital video-recordings. Based on the assessments, intra-rater reliability, inter-rater reliability, and construct validity were explored.Results: The intra-rater reliability was good (Cronbach’s α = 0.80), but comparison of results based on direct observations and blinded video-recordings indicated a significant bias favoring consultants (P = 0.022). Inter-rater reliability was very good (Cronbach’s α = 0.93). However, one rater assessing five procedures or two raters each assessing four procedures were necessary to secure a generalizability coefficient of 0.80. The assessment tool demonstrated construct validity by discriminating between trainees and experienced physicians (P = 0.034).Conclusions: Competency in mediastinal staging of NSCLC using EUS and EUS – FNA can be assessed in a reliable and valid way using the EUSAT assessment tool. Measuring and defining competency and training requirements could improve EUS quality and benefit patient care.